Analysis of the Influence of Network Quality and Consumer Satisfaction on Indosat Ooredo Internet Starter Pack Purchase Decisions, a Case Study on Adolescents in Balungtawun Village, Sukodadi District, Lamongan Regency - Rachmad Eka Pristiwadi; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
This study aims to determine the influence of network quality and consumer satisfaction on the purchase decision of Indosat internet starter packs, both partially and simultaneously. In addition, this study also aims to find out the most dominant independent variables that affect purchasing decisions. This study used 100 samples from the adolescent population of Balungtawun Village with purposive sampling technique. The data collection method is carried out through the distribution of questionnaires or questionnaires to adolescent consumers who have purchased or used Indosat Ooredoo internet starter packs. The data analysis techniques used included validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation test, determination coefficient test, t test, and F test. Simultaneously, network quality and consumer satisfaction also have a significant effect on purchasing decisions. The most dominant variable that affects purchase decisions is network quality.